La « querelle des vernis », une controverse sur le nettoyage des peintures au milieu du XXe siècle - Fanny Girard (Les Cahiers de l'École du Louvre)
The “cleaning controversy” is part of the long tradition of controversies over the cleaning of paintings, debates that still reoccur from time to time. Frequently perceived as a conflict between two cleaning practices, complete cleaning and partial cleaning, it is also the context for profound reflection on concepts such as the prudence des interventions, documentation, the training of restorers and the importance of dialogue. It greatly contributed to the development of international and interdisciplinary cooperation in the domain of the conservation and restoration of cultural goods. Dating from the mid-twentieth century and directly preceding the theorisation of modern restoration, the polemic was a moment fort in the elaboration of current principles and practices.